2012
DOI: 10.4028/www.scientific.net/ddf.326-328.696
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Oxygen and Nitrogen in the Ti-15Mo Alloy Used for Biomedical Applications

Abstract: The Ti-15Mo alloy is a promising material for use as a biomaterial because of its excellent corrosion resistance and its good combination of mechanical properties, such as fatigue, hardness, and wears resistance. This alloy has a body-centered predominantly cubic crystalline structure and the addition of interstitial atoms, such as oxygen and nitrogen, strongly alters its mechanical properties. Mechanical spectroscopy is a powerful tool to study the interaction of interstitial elements with the matrix metal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…With the first doping on oxygen (sample Ti–15Mo#3), there was a significant increase in hardness, which can be explained by the fact of α′ phase having been increased and the oxygen concentration being the highest of all conditions; solid solution hardening also may have occurred. This assertion is corroborated by mechanical spectroscopy results [ 16 ], once for the Ti–15Mo#3; although it has the highest oxygen content, the decomposition of relaxation peak shows that the Ti–O and Mo–O processes have little intensity, i.e. , few oxygen atom occupy the interstitial sites, to cause stress-induced ordering of oxygen atoms around titanium and molybdenum.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…With the first doping on oxygen (sample Ti–15Mo#3), there was a significant increase in hardness, which can be explained by the fact of α′ phase having been increased and the oxygen concentration being the highest of all conditions; solid solution hardening also may have occurred. This assertion is corroborated by mechanical spectroscopy results [ 16 ], once for the Ti–15Mo#3; although it has the highest oxygen content, the decomposition of relaxation peak shows that the Ti–O and Mo–O processes have little intensity, i.e. , few oxygen atom occupy the interstitial sites, to cause stress-induced ordering of oxygen atoms around titanium and molybdenum.…”
Section: Resultssupporting
confidence: 64%
“…Although the concentration of α′ phase increased for Ti–15Mo#4 and Ti–15Mo#5 samples, it would be expected to increase hardness, but a decrease occurred. A possible explanation for this observation is that the oxygen has the role of reducing hardness when it is interstitial, which is corroborated by mechanical spectroscopy measures, as Ti–O and Mo–O processes are quite intense [ 16 ]. Thus, it can be observed that the behavior of microhardness on the basis of the quantity of oxygen and α′ phase analyzed independently differs, which means it must be analyzed simultaneously, as each stage of processing varies the microstructure and the oxygen concentration.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations